2020
DOI: 10.7759/cureus.7789
|View full text |Cite
|
Sign up to set email alerts
|

Enterocutaneous Fistula: A Simplified Clinical Approach

Abstract: Tuma et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 30 publications
0
26
0
14
Order By: Relevance
“…The results showed that the AUC of each index was the largest, and the combined monitoring of PCDAI score and the expression of four indexes was of a great value to evaluate the nutritional status of children with CD. However, due to the immature immune system and digestive system of newborns and the influence of age, there are great differences in individual manifestations of infection and inflammation [ 18 ]. So, there were some children's detection indicators even in the normal range, which may cover up the condition.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the AUC of each index was the largest, and the combined monitoring of PCDAI score and the expression of four indexes was of a great value to evaluate the nutritional status of children with CD. However, due to the immature immune system and digestive system of newborns and the influence of age, there are great differences in individual manifestations of infection and inflammation [ 18 ]. So, there were some children's detection indicators even in the normal range, which may cover up the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, non-specific symptoms such as weakness, fever, chills, malaise, poor appetite, and malnutrition can be found. More specific symptoms of this type of fistula are wound discharge, diarrhea, and gastrointestinal (GI) bleeding [ 2 , 5 , 6 ]. From first case, the patient said that there was a discharge in the abdominal area which was sometimes painful.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…The CT scan is very specific in their depiction of the anatomy of the fistula canal and often can exclude any abscess. CT scans can also help to plan the surgical intervention [ 2 , 5 , 6 ].…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quin și colab. găsește că 89,1% din fistulele digestive externe sunt fistule postoperatorii, 6,8% fistule spontane și 3,99% fistule apărute după proceduri endoscopice [8,9]. Majoritatea autorilor se referă de regulă la incidența fistulelor enterocutanate postoperatorii; Jelena Wercka et al [10] dau o incidență a FEC postoperatorii de 5,5%, în timp ce Falconi și Pedrazzoli [11], analizând 120 studii clinic, dau următoarele date referitoare la incidența fistulelor enterocutanate postoperatorii în funcție de tipul operației primare: 0-45% după esofagectomia transhiatală și 1-2% după esofagectomia subtotală, 68% după închiderea perforației gastrice/duodenale cu patch de epiplon și 2-31% după chirurgia cancerului gastric, 1% după coledocojejunoanastomoză și până la 19% după coledoco-duodenoanastomoză, 0-7% (până la 19% după alți autori) după chirurgia colorectală și 3-36% după chirurgia pancreasului.…”
Section: Tabelul Iv-operația Primară șI Tipul Anastomozeiunclassified